Mapping the energy landscapes of supramolecular assembly by thermal hysteresis - Robert W. Harkness V (Nature Portfolio, 2018)
Complex assembly pathways often involve transient, partly-formed intermediates that are challenging to characterize. Here, the authors present a simple and rapid spectroscopic thermal hysteresis method for mapping the energy landscapes of supramolecular assembly.